Incidence density mortality rate among HIV-positive children on antiretroviral therapy in Ethiopia: a systematic review and meta-analysis. - Desalegn Girma; Zinie Abita; Mirresa Guteta; Abinet Abebe; Amanuel Adugna; Melsew Setegn Alie; Gossa Fetene Abebe (BMC, 2024)
Abstract Background Human Immunodeficiency Virus (HIV) continues to be the major cause of childhood deaths, particularly in the sub-Saharan African region. In Ethiopia, though several primary studies have been conducted on the incidence of HIV-related child mortality, the pooled incidence density mortality rate among HIV-positive children is unknown. Therefore, this systematic review and meta-analysis aimed to estimate the pooled incidence density mortality rate among HIV-positive children and identify its associated factors in Ethiopia. Methods We browsed PubMed, HINARI, Science Direct, Google Scholar, African Journals Online, and cross-references using different search terms to identify articles. Quality appraisal was done using the Joanna Briggs Institute checklist. Meta-package was used to estimate the pooled incidence of mortality and hazard ratio (HR) of predictors. Heterogeneity was tested using the I-square statistics. Publication bias was tested using a funnel plot visual inspection and Egger's test. Data was presented using forest plots and tables. The random effect model was used to compute the pooled estimate. Results The overall pooled incidence density mortality rate among HIV-positive children was 2.52 (95% CI: 1.82, 3.47) per 100 child years. Advanced HIV disease (hazard ratio (HR): 3.45, 95% CI (Confidence Interval): 2.64, 4.51), tuberculosis co-infection (HR: 3.19, 95% CI: 2.08, 4.88), stunting (3.22, 95% CI: 2.46, 4.22), underweight (HR: 2.71, 95% CI: 1.72, 4.26), wasting (HR: 4.14, 95% CI: 2.27, 7.58), didn't receive Isoniazid preventive therapy (HR: 3.33, 95% CI: 2.22, 4.99), anemia (HR: 3.03, 95% CI: 2.52, 3.64), fair or poor antiretroviral therapy adherence (HR: 4.14, 95% CI: 3.28, 5.28) and didn't receive cotrimoxazole preventive therapy (HR: 3.82, 95% CI: 2.49, 5.86) were factors associated with a higher hazard of HIV related child mortality. Conclusions The overall pooled incidence density mortality rate among HIV-positive children was high in Ethiopia as compared to the national strategy target. Therefore, counseling on antiretroviral therapy adherence should be strengthened. Regular monitoring of hemoglobin levels and assessment of nutritional status should be done for all children living with HIV. Moreover, healthcare professionals should follow the national HIV treatment guidelines and provide cotrimoxazole preventive therapy and Isoniazid preventive therapy up on the guidelines for children living with HIV. Registration Registered in PROSPERO with ID: CRD42023486902.